CLINICAL RESULTS AFTER INTRA-CAVITARY DRAINAGE OF GIANT BULLAE IN PATIENTS WITH POOR PULMONARY RESERVES - Muhammad Shoaib Lodro,; Mazcuri, Misauq; Tanveer Ahmad,; Ambreen Abid, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Giant bullae (GB) are space occupying lesions associated with chronic respiratory symptoms. The aim of this study is to evaluate outcome of intra-cavitary tube drainage procedures (ITDP) in terms of clinical and radiological benefits. Methods: A prospective study was conducted in The Department of Thoracic Surgery, Jinnah Postgraduate Medical Center, Karachi, from February 2021 to April 2022 after ethical approval. Patients above 12 years, with poor reserve and GB underwent clinical, radiological and laboratory assessment before and after ITDPs to document various studied parameters. Results: A total of 48 patients were included; thirty-two (66.7%) were males. Mean age was 46.7±12.14 years. Most common aetiology was COPD (28; 58.3%). GB were ‰¥10 cm in size in 36 (75%) with right upper lobe involvement in 20 (41.7%). Preoperative dyspnoea score of IV was seen in 41 (85.4%) and chest pain in 42(87.5%) patients. In 34(70.8%) patients, Monaldi procedure and in 14 (29.2%) Brompton technique was used. Dyspnoea score improved from grade IV to II (24/41; p=0.004) along with reduction in pain and cough (p=0.012; p=0.002), respectively. Improvement post operatively in oxygen saturation, forced vital capacity, forced expiratory volume in 1 sec (6.08±1.36%, 0.73±0.516 L and 0.57±0.07 L, respectively, p<0.001) was seen. Partial pressure of oxygen (PaO2) and carbon dioxide improved by 40.6±4.82 (p=0.009) and 13.22±3.62mmHg (p=0.7). Improvement of PaO2 was associated with reduction in the size of bullae (9.33±5.13cm; p=0.006). Radiographical resolution was seen in 41 (87.5%) majorly within 2 months (21; 51.2%). Duration of hospital stay was 4.20 ±0.92 days with no mortality. Complications were seen in 25 (52.1%) patients. Conclusion: intra-cavitary tube drainage procedures allow both clinical and physiological improvement in patients with GB. They allow resolution of bullae in patients with poor reserves and help in expansion of underlying compressed lung, improving both the clinical symptoms and radiological picture.